Fabrication and Characterization of PU-g-poly(HEMA) Film for Clotting Time and Platelet Adhesion - Tarmizi, Z.I. (Institute of Physics Publishing, 2020)
This paper describes a fabrication of poly (2-hydroxylethyl methacrylate) poly(HEMA) grafted on polyurethane (PU) film prepared by radiation-induced grafting (RIG) copolymerization method using electron beam irradiation for the first time. This method was well known to be fast technique, clean method without involve any chemical initiator, chemically bond the materials, and at the same time is a sterile technique suitable for further potential of biomedical application. This poly(HEMA) grafted on PU film or called as PU-g-poly(HEMA) films was analysed using Fourier-transform infrared (FTIR), scanning electron microscope (SEM), water contact angle analyser (WCA), platelet adhesion and clotting time measurement. As the results, poly(HEMA) was confirmed successful grafted on PU based on the shifting of the functional group, no significant changes in surface morphology, lowering the water contact angle from 78.28° to 70.02°, nearly no platelet adhesion and no excessive disturbance of the clotting time was observed. This means that PU-g-poly(HEMA) was improved its hydrophilicity, thus significantly reduced the platelet adhesion and maintain the normal range of time taken for blood to clot. Therefore, the present PU-g-poly(HEMA) films not only improved hydrophilicity, however, was also compatible with blood. Thus, it may be potential candidates in the biomedical devices or new biomaterial useful for future tissue engineering fields. © Published under licence by IOP Publishing Ltd.